Doping effects of Nb on the dielectric properties of (Pb, La, Sr)(Zr, Sn, Ti, Nb)O3 X9R ceramic materials. (3rd October 2019) - Liang, Linlin; Wang, Jing; Song, Aizhen; Wu, Ruifang; Chen, Danyang; Lv, Yunkai
Abstract: With an ever-increasing dependence on temperature-stability for operating at extreme condition, Nb 5+ ions were used as effective dopants to prepare dielectric materials satisfying EIA X9R specifications. Pb0.85 La0.02 Sr0.06 [(Zr0.7 Sn0.25 Ti0.05 )1- x Nb x ]O3 (PLSZSTN) ceramics powders were prepared by wet-chemistry methods. The effects of various Nb 5+ concentrations on phase structure, morphology, temperature stability and dielectric properties were investigated. As the Nb amount is 0.6 mol%, the dielectric constant of capacitance is about 318. The temperature coefficient of capacity varied from −11.63% to 6.68% at the temperature range between −55 °C and 200 °C, with a temperature coefficient of capacitance less than ±15%.